2021
DOI: 10.1371/journal.pone.0248593
|View full text |Cite|
|
Sign up to set email alerts
|

Queen cells acceptance rate and royal jelly production in worker honey bees of two Apis mellifera races

Abstract: Royal jelly (RJ) is an acidic yellowish-white secretion of worker honey bee glands, used as food material of worker bee larvae for the first three days and queen bee larvae for the entire life. It is commercially used in cosmetics and medicinal industry in various parts of the world. This study determined the queen cell acceptance rate and RJ production difference among Italian and Carniolan bee races. Furthermore, the effect of plastic cup cell priming media, diets and seasons were tested on the larval cell a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…99 ± 2.22 mg/cell cup in hygienic bee colonies and, whereas 158.87 ± 2.52 mg/ cell cup in non-hygienic bee colonies. Previous literature indicated a lot of variations in RJ production, larval acceptance, and quality which affected my multiple factors including genetic variations, harvesting time, queen fecundity, and other environmental factor associated to weather condition and feeding conditions [ 21 , 33 , 38 , 48 50 ]. For instance, a previous literature reported that Africanized honeybees have a lot of variation, which opens up the possibility of selecting these honeybees for any production, such as honey, wax, pollen, propolis, or RJ, as happened with European honeybees selected to pollinate alfalfa cultures in the United States [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…99 ± 2.22 mg/cell cup in hygienic bee colonies and, whereas 158.87 ± 2.52 mg/ cell cup in non-hygienic bee colonies. Previous literature indicated a lot of variations in RJ production, larval acceptance, and quality which affected my multiple factors including genetic variations, harvesting time, queen fecundity, and other environmental factor associated to weather condition and feeding conditions [ 21 , 33 , 38 , 48 50 ]. For instance, a previous literature reported that Africanized honeybees have a lot of variation, which opens up the possibility of selecting these honeybees for any production, such as honey, wax, pollen, propolis, or RJ, as happened with European honeybees selected to pollinate alfalfa cultures in the United States [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…UNC80 is essential in drosophila to promote circadian behavioral rhythm [86]. Our recent findings and previous behavioral facts suggest genes involved in caste differentiation, depression; facilitate pathways for neurotransmitters, integumentary system, storage proteins, brain development, sensory processing, and neurodegenerative disorder, which may cause impairment learning and reduce the learning performance in failed-learner bees [87][88][89][90].…”
Section: Plos Onementioning
confidence: 57%
“…It should be noted, however, that the RJ yield for the Africanized bees is much lower, i.e. ∼8 g per two-queen colony, as for other non-RJB races ( Khan et al, 2021 ; Ma et al, 2021 ). Moreover, although colonies with three or more RJB queens have been established by ablating queen mandibles to avoid queen fighting, they are not recommended for commercial RJ production due to special care required for their maintenance ( Zheng et al, 2009 ).…”
Section: Discussionmentioning
confidence: 91%